Organisational citizenship behaviour in non-profit organisations. - Ko, Joanne Pei Lin. (2011)
This study investigates the influence of transformational leadership on organisational citizenship behaviours among employees in non-profit organisations. We conceptualised goal internalisation as a possible mediator in the relationship. Survey data from 156 employees of APSN, a non-profit organisation in Singapore, revealed that transformational leadership is positively associated with organisational citizenship behaviours. Goal internalisation was also found to mediate the relationship. Moreover, employees are more likely to engage in behaviours directly beneficial to the organisation than towards individuals. Implications of this study for theory and practice and directions for future research are also discussed.